Shock Absorber Modelling to Estimate Damping Factor - Hamdzan
Vehicle shock absorbers, in general do not have linear characteristics but usually simplified linearally, is not linear function of its end parts speed. An accurate physical modelling is required to know shock absorber damping characteristic based on its speed variation and excitation frequency. Previous researcher estimates damping value by experiment or use a fix linear function for model examination to see global characteristic of shock absorbers, such as F = C.V. This thesis use more complex or detail modelling that include linear and non linear characterics of its physical phenomena. The model resulted from this thesis is expected can be used as its numerical experiment system or part of a bigger suspension or automotive system. At this thesis, the shock absorber is modeled with complexity level: fluid is modelled by lump, excitation frequency range from low to high value, speed range from low to high, linear effect at stream leakage of tube and piston, nonlinier effect at stream pass through restriction, stream nonlinier effect pass through orifice, cavitation effect, tube elasticity effect, coulomb friction effect, temperature effect, laminar stream and turbulen, and piston inertia and vehicle weight. The modeling can be used as learning way for Indonesian industry of shock absorbers, since modeling explained from simple model using excel spreadsheet and then developed more complex using bond graph, Matlab Simulink and CFD modeling.